Perlindungan Hukum bagi Pekerja Penyandang Disabilitas yang Bekerja di PT X Kota Bandung Dihubungkan dengan Undang-Undang Nomor 8 Tahun 2016 Tentang Penyandang Disabilitas dan Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Ananda Regina Putri; Deddy Effendy (UNISBA Press, 2023)
Abstract. Within the scope of the company, workers with disabilities have the same rights as non-disabled workers, where one of them gets protection in the form of facilities provided by the company to make it easier for workers with disabilities to carry out their work. This research examines